Program Kegiatan Istighosah bagi Wali Murid TK Darul Athfal Sumbersari Kencong Kepung Kediri - Siti Nur Hidayah; Rohmad (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The title of the KKN DR report was written by Siti Nur Hidayah "The Influence of Istighosah Activities On the guardian of Kindergarten Student Darul Atfal Sumbersari Kencong Kepung Kediri". This research is motivated by the emergence of individualistic, egoistic, and materialistic to have an impact in the form of anxiety, anxiety, stress, and depression. Seeing such a reality that has reached the peak of material pleasure actually turns from what is expected, namely they are faced with anxiety. Various problems often have a bad impact on the mental health of individuals that will lead to mental or psychiatric disorders. Istighotsah is one solution to this problem.